APPROXIMATION OF THE DEPENDENCE OF STATIC EXTRACTION FORCE OF SILK FROM COCOON SHELL ON TIME AND TEMPERATURE - Karimov Ravshan Khikmatulayevich (Modern American Journals, 2025)
This article investigates the static extraction of silk from the cocoon shell, focusing on the force required for silk release, the influence of time, and variations in temperature during silk reeling. Our research examines key stages of cocoon preparation for reeling, including the softening of sericin to reduce its adhesive strength, increasing the cocoon’s weight by filling it with water, and locating the continuous silk filament's end. During the reeling process, cocoons are submerged in water, and a certain level of resistance force is needed to counterbalance the silk's tension. A secondary aim of the cocoon preparation process is to increase the weight of the cocoons, which is achieved by saturating their inner cavity with water.
Keywords: Cocoon, silk filament, sericin, silk reeling, cocoon preparation, static and dynamic extraction forces.